Gastrointestinal endoscopy at Amana Municipal Referral Hospital in Tanzania: reasons for referral and findings - Muhumba, Erick; Magafu, Mgaywa G.; Mwita, Julius C.; Mkongo, Eliasa; Mwandri, Michael B. (Tanzania Journal of Health Research, 2015)
Upper gastrointestinal endoscopy is a medical procedure for visualizing and treating diseases in the upper gastrointestinal tract. It is useful in the surveillance, diagnosis and treatment of acute conditions such as gastrointestinal haemorrhages, benign, malignancies or inflammatory conditions. Because of unavailability of specialist doctors, open access endoscopy referral system is the main system practiced in Tanzania. This study was carried out to investigate the appropriateness of referrals for endoscopy and to determine the endoscopic findings at Amana Municipal Referral Hospital in Tanzania. This cross-sectional study was carried out from March 2010 to June 2011 involved patients referred for endoscopy. Demographic characteristics, reasons for referral and endoscopic findings were recorded for each patient. A total of 393 patients were involved in the study. The mean age of the study subjects was 47.3±17.4 years. The main reasons for referral were epigastric pain (57%), vomiting blood (23%) and difficult in swallowing (20%). The most common endoscopic findings were gastritis (57.2%), oesophagitis (10.2%) and gastric tumours (6.5%). The main reasons for endoscopy referrals at Amana Municipal Referral Hospital are epigastric pain, difficult in swallowing and vomiting blood. The normal endoscopy findings observed falls within normal range. These findings are important for further development of the endoscopy unit, for streamlining services, training of the required skills, and for planning.